FACTORS AFFECTING SECOND LANGUAGE ACQUISITION IN THIRD-GRADE STUDENTS IN SABILUL HUDA ISLAMIC PRIMARY SCHOOL - Fath, Fatiha Nuur (CALL, 2022)
There are several aspects that influence the acquisition of English by third-grade children during online schooling. Respectfully, this research is eager to prove the psychological and social aspects that affect second language acquisition. This study uses qualitative descriptive method and the researcher as a participant observer. The data in this study are third-grade students of Sabilul Huda Islamic Primary school while online schooling. The data are collected through interviews, observation method, and documentation. Then, theory of second language acquisition is involved in analyzing data to answer the research problems. In the final result, several factors that impact third-grade students to acquire English verbs are psychological and social aspects; this influences online learning during the covid-19 pandemic. The process of learning and teaching English also influences the acquisition of English in third-grade students during online schooling. Learning English material appropriately and can be understood by third-grade students is a supporting factor for them to acquire English verbs.Â Keywords: second language acquisition, psychological and social factors